CAMP signalling and its role in host cell invasion by malaria parasites. (December 2020) - Perrin, Abigail J; Patel, Avnish; Flueck, Christian; Blackman, Michael J; Baker, David A
Highlights: cAMP signalling is essential for invasion of red blood cells by malaria parasites. cAMP regulates phosphorylation of many essential merozoite proteins, including AMA1. cGMP and cAMP signalling interact to co-ordinate egress then invasion respectively. Recent work has advanced understanding of the enzymes involved in both pathways. Abstract : Cyclic adenosine monophosphate (cAMP) is an important signalling molecule across evolution, but until recently there was little information on its role in malaria parasites. Advances in gene editing – in particular conditional genetic approaches and mass spectrometry have paved the way for characterisation of the key components of the cAMP signalling pathway in malaria parasites. This has revealed that cAMP signalling plays a critical role in invasion of host red blood cells by Plasmodium falciparum merozoites through regulating the phosphorylation of key parasite proteins by the cAMP-dependent protein kinase (PKA). These insights will help us to investigate parasite cAMP signalling as a target for novel antimalarial drugs.